SUPPLY AND DEMAND CARRYING CAPACITY IN DEVELOPING PARK AND RIDE SCHEME IN EAST CORRIDOR OF BANDUNG CITY (CILEUNYI DISTRICT AND ITS SURROUNDING) - Miharja, Mimimg; Pradhitasari, Handini; Dwiputri, Marselly (FSTPT Indonesia, 2015)
Bandung strategic position causes an interdependences of its surrounding the cities, including Cileunyi District which triggers suburbanization and comuting activity. Vast movement from the commuters needs to be comprised without enlarging supply by transportation demand management (TDM) scheme. TDM concept proposed in this study is a park and ride scheme using the shuttle bus modes. In this paper, we examine both demand and supply carrying capacity through a descriptive exploratory method. Carrying capacity identified by the willingness of potential users to pay for the facilities. The willingness of users to pay parking fees is about Rp. 5,001 - 10.000, while the willingness to pay the bus fare is in the range of Rp. 3,000 to 5,000 . Carrying capacity from the supply side is the availability of parking, terminal, and sufficient road network to carried four route of shuttle bus.